2013
DOI: 10.1039/c2lc41099k
|View full text |Cite
|
Sign up to set email alerts
|

Sample solution constraints on motor-driven diagnostic nanodevices

Abstract: The last decade has seen appreciable advancements in efforts towards increased portability of lab-on-a-chip devices by substituting microfluidics with molecular motor-based transportation. As of now, first proof-of-principle devices have analyzed protein mixtures of low complexity, such as target protein molecules in buffer solutions optimized for molecular motor performance. However, in a diagnostic work-up, lab-on-a-chip devices need to be compatible with complex biological samples. While it has been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…However, other motor systems, such as the kinesin-microtubule system, may also be used, enabling wide applicability due to different dependence of motor function on surface chemistry (cf. ref (36)) for the two systems. Furthermore, other detectors should be possible to study by similar approaches.…”
Section: New Methods For Evaluating Biosensor Performancementioning
confidence: 99%
“…However, other motor systems, such as the kinesin-microtubule system, may also be used, enabling wide applicability due to different dependence of motor function on surface chemistry (cf. ref (36)) for the two systems. Furthermore, other detectors should be possible to study by similar approaches.…”
Section: New Methods For Evaluating Biosensor Performancementioning
confidence: 99%
“…This is a concern as we recently [22] found that both actomyosin and microtubule-kinesin sliding velocity is effectively reduced or inhibited by body fluids (blood components, cell lysates) unless diluted 100–200 times. This finding is expanded on in Figure 1 where we, in addition to effects on velocity, also show concentration-dependent effects of serum on the fraction of motile filaments and on the fraction of independent experiments where actomyosin motility was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Different factors are likely to contribute to the deleterious effects. In addition to serum proteins such as gelsolin, directly depolymerising the actin filaments [27], there may be binding of other blood serum components to HMM or actin [22]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a detection of microvesicles in blood, serum, saliva, and other biological fluids, and analysis of microvesiclecarried cargo pattern represents a novel, noninvasive diagnostic approach (2,(20)(21)(22). In this regard, lab-on-a-chip systems represent a promising and intriguing method using molecular motor-driven diagnostics for sensitive detection of biomarkers in extremely small sample volumes (23). We recently investigated high-capacity nanocarriers, such as actin filaments or bundles, for microvesicle detection (24).…”
Section: Introductionmentioning
confidence: 99%